1987
DOI: 10.2302/kjm.36.298
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of bifidobacterium preparations on pediatric intractable diarrhea.

Abstract: We investigated the effects of administration of Bifidobacterium prepara tions and commercially available Bifidus Yogurt on infantile intractable diarrhea. Fifteen patients with intractable diarrhea were treated from 1982 to 1985. These patients (11 boys and 4 girls) ranged in age from 1 month to 15 years (mean 2.5 years) and received antibiotic therapy for the treatment of such diseases as septicemia and respiratory tract infections. During treatment, waterly diarrhea appeared and lasted for 1 to 10 weeks (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…This meant that the metabolic activities of intestinal flora re- turned to physiological conditions and the balance between the host and its intestinal physiology also returned to normal. In summary, as described in more detail elsewhere (11) , malabsorption of water and electrolytes, probably induced by antibiotic therapy, may be corrected through normal floral metabolic activities such as organic acid fermentation, bile acid metabolism, and utilization of mucin, resulting in a cure of diarrhea.…”
Section: Impact Of Administration Of Bifidobacterium On the Recovery mentioning
confidence: 95%
See 2 more Smart Citations
“…This meant that the metabolic activities of intestinal flora re- turned to physiological conditions and the balance between the host and its intestinal physiology also returned to normal. In summary, as described in more detail elsewhere (11) , malabsorption of water and electrolytes, probably induced by antibiotic therapy, may be corrected through normal floral metabolic activities such as organic acid fermentation, bile acid metabolism, and utilization of mucin, resulting in a cure of diarrhea.…”
Section: Impact Of Administration Of Bifidobacterium On the Recovery mentioning
confidence: 95%
“…Recently, we investigated the effects of administration of Bifidobacterium preparations on infantile intractable diarrhea (11) . Fifteen patients (11 boys and 4 girls), ranging in age from 1 month to 15 years (mean 2.5 years), were receiving antibiotic therapy for the treatment of such diseases as septicemia and respiratory tract infections.…”
Section: Impact Of Administration Of Bifidobacterium On the Recovery mentioning
confidence: 99%
See 1 more Smart Citation
“…Tojo et al found that the long-term administration of Bifidobacterium breve was effective in decreasing the bacterial counts in the stool of patients infected with Campylobacter jejuni and in normalizing the intestinal flora of these patients (15). Hotta et al reported that the serial oral administration of bifidobacteria preparations was effective in the symptomatic treatment of infants with severe diarrhea and in the normalization of their intestinal flora (6). In previous studies, we confirmed that the serial administration of norfloxacin to germ-free mice infected with E. coli O157:H7 enhanced the production of verotoxins and resulted in the death of the mice (8).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of diarrhoeic symptoms has been associated with the lowering of intestinal transit, and modification of the composition and metabolism of the microflora (Hotta et al 1987;Pochart et al 1989;Marteau et al 1990;Kaila et al 1992;Shermak et al 1995). Antimutagenic effects of dairy products are explained by a decrease in some enzymic activities (Goldin et al 1980(Goldin et al , 1992Goldin & Gorbach, 1984a,b;Lidbeck & Nord, 1991;Bartram et al 1994), and hypocholesterolemic properties have been correlated with their ability to metabolise cholesterol and bile salt (Gilliland et al 1985;Gilliland & Walker, 1990;Walker & Gilliland, 1993;Buck & Gilliland, 1994).…”
mentioning
confidence: 99%